2019
DOI: 10.1128/mbio.01766-19
|View full text |Cite
|
Sign up to set email alerts
|

An Amyloid Core Sequence in the Major Candida albicans Adhesin Als1p Mediates Cell-Cell Adhesion

Abstract: The human fungal commensal Candida albicans can become a serious opportunistic pathogen in immunocompromised hosts. The C. albicans cell adhesion protein Als1p is a highly expressed member of a large family of paralogous adhesins. Als1p can mediate binding to epithelial and endothelial cells, is upregulated in infections, and is important for biofilm formation. Als1p includes an amyloid-forming sequence at amino acids 325 to 331, identical to the sequence in the paralogs Als5p and Als3p. Therefore, we mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…C. albicans Als1 shares the same sequences of the amyloid core and T domains with Als5, rendering their similarities highly predictable. Experimental studies have indeed confirmed that both adhesins show the same characteristics of cell-to-cell binding initiated by shear-mediated [ 6 , 38 , 43 , 44 , 45 ]. Further, cell-to-cell adhesion occurs with the highest probability and strength when both cells express Als1 with the wild-type cross-β core sequence, while cells that express the non-amyloid substitution V326N have reduced adhesion probability and strength [ 38 ].…”
Section: Other Adhesinsmentioning
confidence: 80%
See 1 more Smart Citation
“…C. albicans Als1 shares the same sequences of the amyloid core and T domains with Als5, rendering their similarities highly predictable. Experimental studies have indeed confirmed that both adhesins show the same characteristics of cell-to-cell binding initiated by shear-mediated [ 6 , 38 , 43 , 44 , 45 ]. Further, cell-to-cell adhesion occurs with the highest probability and strength when both cells express Als1 with the wild-type cross-β core sequence, while cells that express the non-amyloid substitution V326N have reduced adhesion probability and strength [ 38 ].…”
Section: Other Adhesinsmentioning
confidence: 80%
“…The zipper requires homologous interactions to maintain both the intra- and inter-sheet associations, so sequence identity is key. Thus, these bonds are expected to be strong and highly stable, as observed in assays in vitro [ 6 , 37 , 38 ]. These characteristics were recognized and named ‘SRS adhesions’ for strong reversible specific two decades ago [ 37 ].…”
Section: Biogenesis Of Cross-β Bonds In Transmentioning
confidence: 99%
“…One of the key players in C. albicans biofilm formation is the Als3 protein ( Zhao et al, 2004 ; Nobile et al, 2006 ), a member of the agglutinin-like sequence ( ALS ) family which is only expressed during the hyphal or pseudo-hyphal phase ( Hoyer et al, 2008 ; Hoyer and Cota, 2016 ). Another ALS family member, ALS1 , shows 81% sequence homology to ALS3 and has overlapping functions but different expression patterns ( Hoyer et al, 1998 ; Liu and Filler, 2011 ; Ho et al, 2019 ). Remarkably, a C. albicans ALS3 deletion strain is only impaired in biofilm formation in vitro but not in vivo , presumably due to the activation of additional adhesin genes, such as ALS1 ( Nobile et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Lipke, Dufrêne and colleagues developed a new pipette technology called Fluidic Force microscopy enabling to measure forces between single cells [4]. Using this methodology, these authors showed that amyloid-forming sequences have a dual role, namely in the formation of adhesin clusters (nanodomains), which correspond to cis-interactions between molecule of the same cell, and in homophilic adhesion between adhesins on opposing cells (transinteraction) [5,6].…”
Section: Introductionmentioning
confidence: 99%